6-[(2S,3R)-3-(2,4-Difluorophenyl)-3-hydroxy-4-(1H-1,2,4-triazol-1-yl)butan-2-yl]-5-fluoropyrimidine-4-carbaldehyde - Joana L. C. Sousa; Hélio M. T. Albuquerque; Artur M. S. Silva (Molbank, 2023)
Voriconazole (VN) is an antifungal drug indicated for the treatment of several fungal infections. Due to its side effects, some works involving late-stage functionalization of VN have been reported in the literature. Here, we disclose a new VN derivative, the 6-[(2S,3R)-3-(2,4-difluorophenyl)-3-hydroxy-4-(1H-1,2,4-triazol-1-yl)butan-2-yl]-5-fluoropyrimidine-4-carbaldehyde (VN-CHO). This compound results from the photoredox-catalyzed hydroxymethylation of VN, affording a hydroxymethylated derivative (VN-CH2OH), followed by oxidation of the former CH2OH group. VN-CHO was obtained in good yield (70% yield) and its structure was unveiled by 1D (1H and 13C) and 2D (HSQC and HMBC) NMR techniques. The introduction of a formyl group in VN structure creates a very promising site for further functionalization in a molecule which originally does not have many active sites.